2020
DOI: 10.1186/s40779-020-00235-x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of fever and response to antipyretic therapy in military personnel with adenovirus-positive community-acquired pneumonia

Abstract: Background: In 2014, an outbreak of adenoviral pneumonia occurred in the Korean military training center. However, there are limited data on the characteristics of the fever and its response to antipyretic therapy in immunocompetent adults with adenovirus-positive community-acquired pneumonia (CAP). Methods: The medical records of the patients who were admitted to the Armed Forces Chuncheon Hospital for the treatment of CAP between January 2014 and December 2016 were retrospectively analyzed. The patients were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Compared to non-adenoviral pneumonia, our results showed that patients with HAdV-55 pneumonia had a prolonged hospital stay and fever, while showing more frequent abnormal laboratory findings. In the previous studies on HAdV pneumonia among Korean military personnel, respiratory failure occurred in a considerable number of patients (26,27). In the present study, the adenoviral group also showed increased concentrations of IL-6, IL-8, IL-10, and IFN-γ, suggesting more active cytokine-mediated inflammations than in non-adenoviral pneumonia.…”
Section: Discussionsupporting
confidence: 66%
“…Compared to non-adenoviral pneumonia, our results showed that patients with HAdV-55 pneumonia had a prolonged hospital stay and fever, while showing more frequent abnormal laboratory findings. In the previous studies on HAdV pneumonia among Korean military personnel, respiratory failure occurred in a considerable number of patients (26,27). In the present study, the adenoviral group also showed increased concentrations of IL-6, IL-8, IL-10, and IFN-γ, suggesting more active cytokine-mediated inflammations than in non-adenoviral pneumonia.…”
Section: Discussionsupporting
confidence: 66%
“…Laboratory tests showed that the leukocytes were normal or decreased, and/or the lymphocytes decreased. Chest imaging revealed typical features of viral pneumonia [10]. Wang et al reported that among the 138 investigated patients, 36 received ICU care, with a mortality of 4.3 %.…”
Section: Backgroudmentioning
confidence: 99%
“…characteristics of adenovirus pneumonia (25). Another report confirmed the fever duration associated with SAP was prolonged relative to that of mild-moderate pneumonia (26).…”
Section: Discussionmentioning
confidence: 82%